Pulmonary expansion manoeuvres compared to usual care on ventilatory mechanics, oxygenation, length of mechanical ventilation and hospital stay, extubation, atelectasis, and mortality of patients in mechanical ventilation: A randomized clinical trial - da Silva, Karina; Oliveira, Cristino Carneiro; Cabral, Leandro Ferracini; Malaguti, Carla; José, Anderson (PloS one, 2023)
Pulmonary expansion manoeuvres are therapeutic techniques used to prevent and reverse atelectasis; however, no randomized controlled trials have provided evidence supporting the use of this intervention among individuals on mechanical ventilation. Objective: To evaluate the effects of chest compression-decompression and chest block manoeuvres compared to usual care among patients on mechanical ventilation. Methods: The current study was a randomized clinical trial of adult subjects on mechanical ventilation for 12 to 48 hours. The control group received usual care (passive or active mobilization, manoeuvres for airway clearance and tracheal aspiration). The intervention group received usual care plus two lung expansion manoeuvres, i.e., chest decompression and chest block, while remaining on mechanical ventilation. Assessments were performed before and after usual care, immediately after the intervention and 30 minutes after the intervention. The primary outcome was static compliance. The secondary outcomes were the incidence of atelectasis, dynamic compliance, airway resistance, driving pressure, oxygenation, duration of mechanical ventilation, extubation success, length of hospital and ICU stay, and mortality. Results: Fifty-one participants (67±15 years old, 53% men, 26 in the control group and 25 in the intervention group) were evaluated. No differences in static compliance were observed between groups (intervention minus control) before and after expansion manoeuvres [3.64 ml/cmH 2 O (95% CI: -0.36–7.65, p = 0.074)]. Peripheral oxygen saturation differed between groups before and after expansion manoeuvres, with more favourable outcome observed in the control group [-1.04% (95% CI: -1.94 –-0.14), p = 0.027]. No differences were found in other outcomes. Conclusion: Chest compression-decompression and chest block manoeuvres did not improve ventilatory mechanics, the incidence of atelectasis, oxygenation, the duration of mechanical ventilation, the length of stay in the ICU and hospital, or mortality in individuals on mechanical ventilation. The findings of this study can be valuable for guiding evidence-based clinical practice and developing a therapeutic approach that provides real benefits for this population.